2021
DOI: 10.3390/biomedicines9111649
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Computational Study of the GroEL–Prion Protein Complex

Abstract: The molecular chaperone GroEL is designed to promote protein folding and prevent aggregation. However, the interaction between GroEL and the prion protein, PrPC, could lead to pathogenic transformation of the latter to the aggregation-prone PrPSc form. Here, the molecular basis of the interactions in the GroEL–PrP complex is studied with cryo-EM and molecular dynamics approaches. The obtained cryo-EM structure shows PrP to be bound to several subunits of GroEL at the level of their apical domains. According to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Molecular dynamics was carried out at neutral pH using the GROMACS package [ 45 ] version 2020.1 and the a99SB-disp force field [ 46 ], which is used to model both structured and unstructured proteins [ 47 ]. An integration time step of 2 fs was used, and three-dimensional periodic boundary conditions were imposed.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular dynamics was carried out at neutral pH using the GROMACS package [ 45 ] version 2020.1 and the a99SB-disp force field [ 46 ], which is used to model both structured and unstructured proteins [ 47 ]. An integration time step of 2 fs was used, and three-dimensional periodic boundary conditions were imposed.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies including the works of our group have visualized the interaction of monomers of a prion protein cellular isoform with the bacterial chaperonin GroEL ( Figure 1 ) [ 85 ]. This interaction with GroEL in the absence of GroES leads to the amyloid transformation of PrPc, resulting in the formation of large amyloid aggregates [ 57 ].…”
Section: Influence Of Chaperones On Pathological Transformation Of Am...mentioning
confidence: 99%
“…Thus, it was shown that prion protein monomers bind in the internal cavity of the GroEL chaperonin. Such binding decreases the flexibility of the chaperonin ring in which the prion protein is bound [ 85 ]. The interaction of PrPc with GroEL disturbs the functioning of the GroEL–GroES complex: the chaperonin loses its ability to reactivate denatured GAPDH [ 86 ].…”
Section: Blocking Of Chaperones By Misfolded Proteins and Amyloidogen...mentioning
confidence: 99%
“…Structural studies of different substrates bound to nucleotide-free GroEL have been published, including malate dehydrogenase (9), gp23 (10), PepQ (11), Rubisco (12), actin (13), and PrP (14). Together, these studies show that non-native proteins initially bind multivalently and in different configurations to GroEL apical domains, allowing GroEL to capture structurally distinct folding intermediates.…”
Section: Introductionmentioning
confidence: 99%